Case Report: Effect of Ajwa Dates on Neutrophil Lymphocyte Ratio of Perimenopausal Women - Ashari, Anjelia Farmana; Mappaware, Nasrudin Andi; Basyar, Basyar; Hamsah, M.; Royani, Ida; Hidayati, Prema Hapsari (Newinera Publisher, 2024)
Perimenopause, certain hormone levels begin to decrease, especially hormones related to female reproduction, namely the hormones estrogen and progesterone. Estrogen deficiency can cause complaints such as urinary tract infections. The neutrophil lymphocyte ratio is a laboratory parameter that has the potential to be a predictor of bloodstream infection or bacteremia in patients with suspected infection. then bacterial infection can cause systemic inflammation characterized by fever. The high content of polyphenols, flavonoids and flavones contained in Ajwa dates. One of the high levels of flavonoids in dates is a good anti-inflammatory agent. Ajwa extract which contains ethyl acetate, methanolic and water can inhibit the lipid peroxidase enzyme cyclooxygenase (COX-1 and COX-2).